Karyomegalic interstitial nephritis, a fascinating histopathologic entity for pathologists: Be watchful of the FAN1 gene mutations - Gurpreet K. Walia; Mahesha Vankalakunti; Ramanjit S. Akal; Vijoy K. Jha (Indian Journal of Pathology and Microbiology)
Karyomegalic interstitial nephritis (KIN) is an uncommon autosomal recessive disease, which is characterized by enlarged and hyperchromatic nuclei of the renal tubular epithelial cells. It is associated with mutations in Fanconi anemia-associated nuclease 1 gene, which is responsible for DNA repair, and these pathogenic mutations are responsible for progressive renal failure in young adults. We present a case of a 29-year-old female with end-stage renal disease who had a family history of early-onset renal failure in two of the siblings. Her elder sister with chronic kidney disease stage III was advised to be biopsied to look for any familial causes. Stained sections of renal biopsy revealed normal glomeruli. Tubular epithelial cells showed nuclear changes focally like hyperchromasia, karyomegaly, and anisonucleosis. On direct immunofluorescence, all glomeruli were negative for deposits with all antisera. Based on these findings, a final opinion of KIN was given.